Investigation of the impact of planar microelectrodes on macrophage-mediated mesenchymal stem cell osteogenesis - Chen, Hui; Xu, Chuchu; Huang, Qin; Chen, Yuhua; Cheng, Kui; Wang, Huiming; Chen, Xiaoyi (Frontiers in Cell and Developmental Biology, 2024)
Osseointegration commences with foreign body inflammation upon implant placement, where macrophages play a crucial role in the immune response. Subsequently, during the intermediate and late stages of osseointegration, mesenchymal stem cells (MSCs) migrate and initiate their osteogenic functions, while macrophages support MSCs in osteogenesis. The utilization of ferroelectric P(VDF-TrFE) covered ITO planar microelectrodes facilitated the simulation of various surface charge to investigate their effects on MSCs' osteogenic differentiation and macrophage polarization and the results indicated a parabolic increase in the promotional effect of both with the rise in piezoelectric coefficient. Furthermore, the surface charge with a piezoelectric coefficient of -18 exhibited the strongest influence on the promotion of M1 polarization of macrophages and the promotion of MSCs' osteogenic differentiation. The impact of macrophage polarization and MSC osteogenesis following the interaction of macrophages affected by surface charge and MSC was ultimately investigated. It was observed that macrophages affected by the surface charge of -18 piezoelectric coefficient still exerted the most profound induced osteogenic effect, validating the essential role of M1-type macrophages in the osteogenic differentiation of MSCs.